(untitled) (Altre Modernità, 2022)
Programmed on techno-scientific basis, the European city of the third millennium risks to forget or trivialize the destructions and mass slaughters brought about by the Second World War. Durs Grünbein’s poetics of the frottage shows how this denial fails to account for life in all its unique expressions making European cities a backdrop of camouflages. The cosmopolitanism pursued by Grünbein roots him in Dresden and Hellerau as places, where both Lebensreform and education for everyone were made possible. Fantasied and phantomised as a possibility for the future, the images of Grünbein’s childhood and adolescence punctuate and even haunt his works. Together with Piazza del Campo and with the pursuit of genius loci. The Island that does not exist becomes, in the poetics of the German-speaking author, the frame of a representability for European citizenship nourished by the ideal instances inspired by the Ventotene Manifesto (1941) and the Hertenstein Colloquies (1946).